IDENTIFICATION OF ACTOR ROLES IN ENDOGENOUS DEVELOPMENT OF RURAL AREAS: KASONGAN VILLAGE STUDY CASE - Bahar, Teddy Kurniawan; Rauf, Mega Hardiyanti; Hidayatullah, Muhammad Luthfi (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2023)
Endogenous Development through creative economy applications is a strategy that had been implemented by many local governments to increase the competitiveness level of a product and human capital in a rural region. The development will be implemented effectively if supported with activities that put forward the collaborative aspect in the governance planning process between policymakers, implementors, and the local community. The distribution of roles and authorities between every participating actor will create a strong and reliable network for more sustainable development. The actors come from the government, local communities, the business sector, and educational institutions. Kasongan is a village with a local industry specializing in earthenware manufacture that has been distributed to domestic and global consumers. The primary stakeholder in this development comes from local artists who applied their creativity to create earthenware products as artistic pieces. This development eventually grows stronger and gained support from secondary stakeholders through training facilities, prioritized programs, and knowledge transfer about the art of crafting. With the identification through stakeholder analysis, it can be concluded that artists, craftsmen, local government, and educational institutions have the most important role as key players on endogenous development in Kasongan.